ANALISIS HUKUMAN MATI DI INDONESIA DI TINJAU DARI PRESPEKTIF HAK ASASI MANUSIA - Rizky Ramadhan Adi Wijaya; Mitro Subroto (RIO LAW JURNAL, 2021)
This study aims to determine the regulation of the death penalty in Indonesia, the regulation of human rights in Indonesia and the implementation of the death penalty in Indonesia from the perspective of human rights. This study uses a type of juridical-normative research through a status approach and library research by conducting an assessment of laws and regulations, books, and several scientific works related to this research. The results of this study indicate that the legislation in Indonesia still recognizes the death penalty as one of the main criminal offenses. The death penalty imposed by the Indonesian government has generated mixed controversies. The death penalty in Indonesia creates two conflicting camps between the pros and cons of the death penalty